Shoot Induction of Black Stem Potato (Solanum tuberosum L. var. Cingkariang) with Several Concentration of 6-Benzylaminopurine (BAP) - Yulianti, Sisi; Noli, Zozy Aneloi; Idris, M. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Black stem potato (Solanum tuberosum L. var. cingkariang/cingkariang potato) are a specific germplasm of West Sumatra with low productivity. One method of propagating this plant is through tissue culture techniques. The addition of Plant Growth Regulator (PGR) determines the results of plant propagation through tissue culture technique. Cytokinins such as 6-Benzylaminopurine (BAP) play a role in cell division and accelerate shoot formation. This study expects to decide the impact of a few convergences of BAP on the shoot enlistment of cingkariang potato. The examination utilized a totally randomized plan (CRD) with four treatments (0, 1, 2, and 3 mg/L BAP) and six replications. The result showed that BAP was able to induce Cingkariang potato shoots in all concentration. BAP 2 mg/L gave the fastest shoot and root emergence time and also gave the highest number of shoots and roots of Cingkariang potato. BAP 2 mg/L was the best concentration for shoot induction of black stem potato (Solanum tuberosum L. var. Cingkariang).